The success of apprenticeships : views of stakeholders on training and learning - Cerdin, Jean-Luc; Peretti, Jean-Marie (London : ISTE, Ltd. ; Hoboken : Wiley, 2020)
Apprenticeships can offer apprentices, their teacher-tutors and business apprenticeship supervisors experiences that are rich in knowledge. The Success of Apprenticeships presents the observations and opinions of 48 actors regarding apprenticeships. These testimonies recount how apprenticeships allowed them to improve their expertise, their professional practices and their organization skills. This book also examines how their interactions in the work/study process allowed them not only to develop the skills of apprentices, but also the skills of those who accompanied them - the teacher-tutors and the business apprenticeships supervisors. The creation of an authentic community of apprentices subscribes to the formation of an ecosystem of learning, in which each individual harvests fruits in terms of the development of their personal abilities.
6. Apprenticeships, a "Springboard" to Professional Integration? -- 6.1. Introduction -- 6.2. Work-linked training -- 6.3. Follow-up and role of the tutor or apprenticeship manager -- 6.4. Autonomy and confidence building? -- 6.5. Better professional integration -- 6.6. Managing the pace of the work-linked training -- 6.7. Conclusion -- 6.8. References -- 7. Reflexivity and Management Apprenticeships -- 7.1. Introduction -- 7.2. From reflexivity to reflexive manager? -- 7.3. Initial training: from a "classical" learning posture to a reflective posture
7.4. In continuous training: a pre-existing professional activity to facilitate the reflective process
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on May 18, 2020).
John Wiley and Sons
Keywords: Apprenticeship programs; Apprentices; Apprentissage professionnel; Apprentis; apprentices; Apprentices; Apprenticeship programs